Board-level employee representation in the UK: Is it really coming? Recent developments and debates - Lionel Fulton (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2019)
In the United Kingdom there are currently no statutory regulations on company workers' participation. Generally speaking, UK companies have a monistic governance structure with a board of directors. Theresa May (former prime minister) announced that in future workers were to have representatives on the board, but little of this promise seems to have been realised. Nevertheless, a revision of the British corporate governance code that came into force in 2019 makes the prospect of workers' representation on boards of directors more likely than at any time in the past 40 years. Listed companies will henceforth be able to choose between three options for involving the employees. In practice, only the occasional workers' representative has been appointed to a board of directors, but new life does seem to have been injected into the debate and the TUC is now calling for at least one-third worker representation on the board of directors.
Keywords: 330